Flower seed production for remunerative returns under poplar based agroforestry system - Rani, Sangeeta; Chauhan, S.K.; Dhatt, Kirandeep; Sharma, Rajni; Babuta, Ritu (Indian Journal of Agroforestry, 2020)
Low returns from traditional crops, over exploitation of natural resources and the ever-increasing demand for fuel, fodder and timber are the main reasons that compel farmers to integrate trees into the farmland. Poplar tree based agroforestry is emerging as one of the diversification options for the farmers in irrigated agro-ecosystem in north western states of India because a highly lucrative market for its timber is readily available. To make the poplar (Populus deltoides) based agroforestry systems economically more profitable, twelve winter flower annuals were evaluated in comparison to traditional wheat crop. Results of the study revealed that yield and other parameters of flowering annuals and wheat crop were comparatively low in association with poplar than in open conditions. Flowering annuals like Coreopsis tinctoria, Coreopsis lanceolata, Phlox drumondii and Gaillardia pulchelia showed better performance than the other flowering annual crops in both the conditions. Study showed that flower seed production of these species under poplar canopy is quite remunerative than growing traditional wheat crop. The tree growth performance was also found better under agroforestry plantation than without intercropping.